Influence of the thermal shock and pre-sprouting on potato tuber yield - Eremeev, V.; Jõudu, J.; Lääniste, P.; Mäeorg, E.; Selge, A.; Tsahkna, A.; Noormets, M. (Spanish Journal of Agricultural Research, 2008)
Thermal shock and pre-sprouting increase the initial development of potato (Solanum tuberosum L.) plants, allowing for earlier harvests. Growing early potatoes without pre-sprouting is not economically viable under Nordic climatic conditions. The aim of this research was to determine how seed tuber pre-planting treatments (untreated, thermal shock and pre-sprouting) influence time to emergence, mean tuber weight, the number of tubers per plant, and yield (including yield dynamics). The main findings of this work were that thermal shock shortened the time to emergence by 2-5 days, while pre-sprouting shortened it by 7-12 days. In addition, thermal shock significantly increased the number of tubers produced, although their mean weight was lower than that of the tubers produced by the pre-sprouted plants. The presprouted tubers provided a very early harvest of large tubers; the harvest time for the thermal shock-treated tubers was a little later. The untreated seed tubers were the last to produce harvestable plants.